The impact of electronic collaboration on learning outcomes - Yussif, A.-S. (Institute of Electrical and Electronics Engineers Inc., 2016)
Even though the effectiveness of e-collaboration has been empirically confirmed, some researchers and educators still find it a challenge in leading to meaningful learning outcomes. The main goal of this study is to explore the relationship between e-collaborative learning experience and students learning outcomes with moderating and mediating effects of social, teaching and cognitive presences. The study intends to investigate whether e-collaborative learning experience with social, teaching and cognitive presences as the mediator and moderator constructs are predictors of students learning outcomes. The Community of Inquiry (CoI) survey instrument, collaborative learning questionnaire and pre-test-post-test questions were used to collect data through an experimental research design involving 60 students. The results show that the constructs of the hypothesized model are reliable and valid. The results from structural equation modeling also demonstrated that e-collaborative learning experience strongly predict learning outcomes indirectly through the mediating and moderating effects of the three presences. Â© 2016 IEEE.